Sektor Ekonomi Potensial Di Kota Tangerang Selatan - Uki Masduki (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2014)
This study aims to determine the potential sectors or sectors base and non-base in the city of South Tangerang. Data obtained through secondary data, that is data Gross Domestic Product (GDP) of South Tangerang City in 2010 - 2013. The data were analyzed using analysis tools Location quotients (LQ) and Growth Ratio Model (MRP). These results indicate, there are five sectors at the same base as the dominant sector which needs to be developed, namely: the building sector, trade, hotels and restaurants, transport and communications, financial services, leasing and business services, and the services sector. Sector is based on the calculation basis of positive LQ (LQ> 1) and the results of calculation of the five sectors Growth Ratio (RPs) through MRP is also positive, or more than one.